Climate parameters analysis as an indication of climate Changes for Diwaniya, Nasiriya, Kut and Karbala meteorological stations - Central and southern Iraq: Karbala climate condition as a case study - Kadum, Weam Hassan; Al-Ali, Iman A. (Iraqi Journal of Science, 2022)
The climate parameters (rainfall, number of rainy days and temperature) data for about seventy years from 1941 – 2009 for three Iraqi meteorological stations (Diwaniya, Nasiriya, and Kut) were investigated and gave good evidence of climate change. As well as the climatic water balance and the climatic conditions were determined at Karbala meteorological station for the years (1982-2015). The annual precipitation for Karbala station-reflect declination from 105 mm for the period 1982-1990 to about 71 mm for the years 2011- 2015 confirms the effect of global climate change. Analyzing Karbala climate parameters reflects that the total annual rainfall is (89 mm), evaporation is (2984 mm), while the mean monthly relative humidity% is 47.9%, sunshine is 8.8 h/day, temperature is 24.1 C and wind speed is 3.0 m/sec. the water surplus in the Karbala area is 8.49 mm, 12.28 mm, and 6.65 mm in December, January and February, respectively. The climate classification of the Karbala area was continental and dry climates, as well as the region, has a significant water deficit of up to 93 % of the total rainfall values.